Oxidative Stress Statue in Follicular Fluid of Infertile Women Treated with IVF/ICSI-ET - Rusul Hashem (Journal of Global Pharma Technology, 2018)
Introduction Oxidative stress (OS) in follicular fluid (FF) may affect in vitro fertilization (IVF) outcomes in infertile women undergoing IVF/ICSI-ET. Aim of study to assess the effects of total peroxide (TPX) concentration, total antioxidant capacity (TAC), oxidative stress index (OSI), malondialdehyde concentration (MDA), glutathione-s-transferase (GST) activity, and superoxide dismutase activity (SOD) on IVF and pregnancy outcomes in PCOS, male cause infertility, and unexplained infertile (UI) patients undergoing IVF cycles. Subjects, material, and methods A prospective case control study was performed among (40) control group (male cause), (40) polycystic ovary syndrome (PCOS) group, and (45) unexplained infertility (UI) group, all of which undergoing IVF/ICSI-ET. FF samples were collected at the day of oocytes aspiration. TPX, TAC, MDA levels, GST, and SOD activities were measured in FF. oxidative stress index were calculated.  Results When control, PCOS and UI groups were compared in term of IVF outcomes, there were no significant differences in M II oocyte, G1 embryo, maturity rate, cleavage rate, fertilization rate, and chemical pregnancy state among the three studied groups (P˃0.05). In addition, comparison of OS parameters among the studied groups showed no significant differences in TAC, MDA, GST activity, GST specific activity, and SOD activity (P˃0.05); however, significant differences in TPX, OSI percentage, and SOD specific activity (P˂0.05) were found. Association analysis between OS parameters and IVF outcomes showed a significant positive correlation between GST activity (and GST specific activity) with G1 embryo, GST activity with pregnancy, as well as, SOD activity and maturity rate in control group (P˂0.05). In addition, GST activity and GST specific activity showed significant positive correlation with both cleavage rate and fertilization rate, GST activity with pregnancy, as well as, TPX with cleavage rate and fertilization rate in PCOS group (P˂0.05). OS parameters in UI group did not show any significant correlation with IVF outcomes (P˃0.05).  When control, PCOS and UI groups were subdivided according to pregnancy outcome, mean TPX and TAC concentrations were higher in pregnant group compared to non-pregnant group; while mean MDA and OSI were lower in pregnant group compared to non-pregnant group in the three studied groups. Antioxidant enzyme activities in pregnant group were higher compared to non-pregnant group in the three studied groups. Conclusion The results of this study demonstrated that the oxidant-antioxidant balance in the oocyte surroundings must be obtained to improve IVF and pregnancy outcomes in patients treated by IVF/ICSI-ET.Keywords: Oxidative stress, Follicular fluid, Polycystic ovary syndrome, Antioxidant, Intra-cytoplasmic sperm injection.